ONCOLOGY NURSING CARE AND QUALIFICATION DEMANDS IN PRIMARY HEALTH CARE - Luciana Martins da Rosa; Ana Izabel Jatobá de Souza; Jane Cristina Anders; Rafaela Nunes da Silva; Gabriela Schutz da Silva; Mayara Cristine Fontão (Universidade Federal do Paraná, 2017)
The objective in this study was to identify the oncology care and qualification demands of nurses working in primary health care. Observational and descriptive study developed at the Health Centers in Florianópolis, Santa Catarina, Brazil. The data were collected between October and November 2015. The research variables were related to education, length of professional experience, care demand and qualification deficiencies in oncology. The study participants were 84 nurses; 41 (48.81%) had graduated more than ten years earlier (12.04±6.99); 46 (54.76%) consider that their learning about oncology at the undergraduate level was insufficient and indicate no further qualification in this area after graduating. The main care and qualification deficiency demands involve the most incident malign tumors, the impact of cancer, oncology therapeutics and their side effects. The data evidence that, despite the experience in primary health care, many professionals feel the need for training that enables them to deliver specialized and qualified care.